Pengkajian Tingkat Kepatuhan Pasien Dewasa tentang Pengobatan Penyakit Tuberkulosis - Asih, Haerunisa; Cholisah, Elis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to assess the suitability of adult patients at Unggul Karsa Medika Hospital with their TB treatment. The research method used is descriptive quantitative research relying on numerical data collected, clarified based on the actual situation in the field, and ultimately used as a basis for drawing conclusions. This research is survey research. Research results from 56 respondents; 52 (or 93%) of these people were following the prescribed anti-tuberculosis drug treatment, whereas only 4 (or 7%) of these people were not. The conclusions from the results of the questionnaire show that Unggul Karsa Medika Hospital personnel have done a good job in educating and guiding TB patients in undergoing treatment. Based on the data, pulmonary TB patients at Unggul Karsa Medika Hospital are in the compliant category. Keywords: Compliance, Anti-TB, Tuberculosis